2001
DOI: 10.1590/s1516-31802001000200002
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporotic fractures of proximal femur: clinical and epidemiological features in a population of the city of São Paulo

Abstract: CONTEXT: It is believed that about 25% of menopausal women in the USA will exhibit some kind of fracture as a consequence of osteoporosis. Fractures of the proximal femur are associated with a greater number of deaths and disabilities and higher medical expenses than all the other osteoporotic fractures together. OBJECTIVE: To study the clinical and epidemiological features of patients with proximal femur fracture in hospitals in São Paulo. DESIGN: Transversal and retrospective study. LOCAL: Hospital São Paulo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
31
0
19

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 34 publications
8
31
0
19
Order By: Relevance
“…The total standardized incidence rate (≥ 60 years) was higher in females and increased progressively with increasing age similar to that in other epidemiological studies. 3,11 The female and total rates in Paraná were superior to the national one, in agreement with the findings of Silveira et al, 11 who believed that the incidence of femur fracture in the elderly is higher in the southern region due to colder temperatures and lower incidence of sunlight, which favors osteoporosis. Taking this into account, we expected that the rate of fractures in Paraná (24º00'S, 51º00W) would be similar to that calculated for the same age group (≥ 60 years) in the city of Marília, São Paulo (50.03 / 10 thousand female inhabitants and 18.73 / 10 thousand male inhabitants) and to exceed Fortaleza's rates (27.5 / 10 thousand female inhabitants and 13/10 thousand male inhabitants); however, we obtained a rate similar to that of Fortaleza (03º 43' S, 38º 32' W)and well below that of Marília (22º 12'S, 49º 56' W).…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…The total standardized incidence rate (≥ 60 years) was higher in females and increased progressively with increasing age similar to that in other epidemiological studies. 3,11 The female and total rates in Paraná were superior to the national one, in agreement with the findings of Silveira et al, 11 who believed that the incidence of femur fracture in the elderly is higher in the southern region due to colder temperatures and lower incidence of sunlight, which favors osteoporosis. Taking this into account, we expected that the rate of fractures in Paraná (24º00'S, 51º00W) would be similar to that calculated for the same age group (≥ 60 years) in the city of Marília, São Paulo (50.03 / 10 thousand female inhabitants and 18.73 / 10 thousand male inhabitants) and to exceed Fortaleza's rates (27.5 / 10 thousand female inhabitants and 13/10 thousand male inhabitants); however, we obtained a rate similar to that of Fortaleza (03º 43' S, 38º 32' W)and well below that of Marília (22º 12'S, 49º 56' W).…”
Section: Resultssupporting
confidence: 86%
“…The study presented results consistent with the literature regarding the higher incidence of fractures in females and in the higher age groups. 3,10,11 The male / female ratio observed of 1: 2.01 was similar to that in Sobral, Ceara (1:1.7), and lower than that in Recife, Pernambuco (1:3.02). Women are more likely to develop osteoporosis and, consequently, fractures as observed in the BRAZOS study.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The socioeconomical impact of fractures on hip region is very strong, leading to increased morbidity and mortality rates. This study evidenced a prevalence of femoral fractures in women (60.29%) and aged people (75.84 years), consistently with literature [17][18][19] Rocha et al 18 found, in a retrospective study on proximal femoral fractures, a mean age of 68.5 years. Female gender showed higher mean ages compared to male gender, with values of 76.912 years for the first group, and 65.69 years for the second one.…”
Section: Discussionsupporting
confidence: 91%
“…Transtrochanteric fractures were prevalent in our study, as well as in the study by Rocha et al 18 , however, other studies show no significant difference between the kind of fracture and higher incidence on males or females. 17 Many factors, not assessed in this study, are involved in simple falls; this kind of trauma remains as the major cause of femoral fractures, totaling 85.30% of the total mechanisms of trauma studied. The presence of comorbidities was an important factor for therapeutic approach, time of hospital stay, for prognosis and change on quality of life.…”
Section: Discussionmentioning
confidence: 90%